Intranasal Oxytocin Blocks Alcohol Withdrawal in Human Subjects - Pedersen, Cort A.; Smedley, Kelly L.; Leserman, Jane; Jarskog, Lars Fredrik; Rau, Shane W.; Kampov-Polevoi, Alexei; Casey, Robin L.; Fender, Trace; Garbutt, James C. (Alcoholism, clinical and experimental research, 2013)
Background The neuropeptide, oxytocin (OT), has been reported to block tolerance formation to alcohol and decrease withdrawal symptoms in alcohol‐dependent rodents. Numerous recent studies in human subjects indicate that OT administered by the intranasal route penetrates into and exerts effects within the brain. Methods In a randomized, double‐blind clinical trial, intranasal OT (24 IU/dose, N = 7) or placebo (N = 4) was given twice daily for 3 days in alcohol‐dependent subjects admitted to a research unit for medical detoxification using Clinical Institute Withdrawal Assessment for Alcohol (CIWA) score‐driven PRN administration of lorazepam. Subjects rated themselves on the Alcohol Withdrawal Symptom Checklist (AWSC) each time CIWA scores were obtained. Subjects also completed the Penn Alcohol Craving Scale, an Alcohol Craving Visual Analog Scale (ACVAS) and the Profile of Mood States (POMS) on inpatient days 2 and 3. Results All subjects had drunk heavily each day for at least 2 weeks prior to study and had previously experienced withdrawal upon stopping/decreasing alcohol consumption. OT was superior to placebo in reducing alcohol withdrawal as evidenced by: less total lorazepam required to complete detoxification (3.4 mg [4.7, SD] vs. 16.5 [4.4], p = 0.0015), lower mean CIWA scores on admission day 1 (4.3 [2.3] vs. 11.8 [0.4], p < 0.0001) and day 2 (3.4 [2.2] vs. 11.1 [3.6], p < 0.002), lower AWSC scores on days 1 and 2 (p < 0.02; p = 0.07), and lower ACVAS ratings (p = 0.01) and lower POMS Tension/Anxiety subscale scores on day 2 (p < 0.01). Conclusions This is the first demonstration that OT treatment may block alcohol withdrawal in human subjects. Our results are consistent with previous findings in rodents that OT inhibits neuroadaptation to and withdrawal from alcohol. OT could have advantages over benzodiazepines in managing alcohol withdrawal because it may reverse rather than maintain sedative‐hypnotic tolerance. It will be important to test whether OT treatment is effective in reducing drinking in alcohol‐dependent outpatients.